Maxillary Sinus Floor Augmentation Using Bovine Bone Grafts With Simultaneous Implant Placement: A 5-Year Prospective Follow-Up Study - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2011)
Purpose: The aim of this study was to evaluate the 5 year clinical results of maxillary sinus floor augmentation using bovine bone grafts with simultaneous implant placement. Material and Methods: A total of 28 patients were enrolled in the study, and a total of 84 implants were placed into the grafted sites. Unilateral or bilateral sinus augmentation was performed, and implants were inserted into the augmented sinuses. After osseointegration and insertion of the prosthesis, the implants were evaluated by clinical and radiographic parameters. Results: The cumulative implant survival rate after 60 months of loading was 100%. Periimplant bone loss was at clinically acceptable levels (0.146 and 0.34 mm after 1 and 5 years, respectively). Conclusions: Bovine bone grafts used in 1-stage sinus augmentation yields sufficient quality and volume of bone for predictable simultaneous implant placement. (Implant Dent 2011; 20: 455-459)
Keywords: bovine grafts; maxillary sinus; oral surgery; sinus augmentation; titanium implants; OSSEOINTEGRATED IMPLANTS; RADIOGRAPHIC EVALUATION; AUTOGENOUS BONE; DENTAL IMPLANTS; ELEVATION; HUMANS; RECONSTRUCTION; OSTEOTOME; HEIGHT